Tinjauan Yuridis Mengenai Fungsi Pengawasan DPRD terhadap Penggunaan Anggaran Pendapatan dan Belanja Daerah (APBD) - Mulyanto, Agus; Laia, Aturkian (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The Regional Revenue and Expenditure Budget (APBD) is central to regional administration, demanding accountability and effective oversight. This study analyzes the legal basis of the Regional House of Representatives’ (DPRD) oversight function regarding APBD utilization; examines its execution across all budgetary phases; identifies normative and practical obstacles; and assesses its effectiveness in preventing misappropriation. Employing a normative legal method with statutory, conceptual, and case approaches, this research analyzes primary legislation alongside relevant secondary materials. The findings reveal that while the DPRD has solid normative authority, its effectiveness is hindered by institutional design issues, limited technical capacity, political interests, asymmetrical data access, and weak follow-up mechanisms. Therefore, strengthening DPRD oversight requires regulatory reform, institutional capacity building, enhanced data support, and integration with external supervision systems to ensure the APBD maximizes public welfare.